Strain variation in bacteriocuprein superoxide dismutase from symbiotic Photobacterium leiognathi. - Dunlap, P V (1986)
Photobacterium leiognathi ATCC 25521 (the type strain and light-organ symbiont of ponyfish) is one of the few bacteria that produces a copper-zinc superoxide dismutase, termed bacteriocuprein. We enzymologically and immunologically characterized the bacteriocuprein superoxide dismutases in sonicates from the type strain and nine additional strains of P. leiognathi, each isolated from the light organ of a separate ponyfish specimen, representing seven ponyfish species. The results indicate considerable strain variation. (i) The level of bacteriocuprein enzymatic activity varied greatly among strains from different species of ponyfish. In four of the nine strains, activity was low or undetectable, while in five strains it was comparable to that in the type strain. (ii) The bacteriocuprein in one strain had a specific activity much lower than that of the type strain, and in another strain, no bacteriocuprein activity and no cross-reactive polypeptide were detectable. (iii) A new electrophoretic variant, which migrated slower than that of strains from fish captured in Thailand and Japan, was identified in strains from fish captured in the Philippine Islands. (iv) Enzymological and immunological differences were observed in bacteriocupreins of strains from male and female specimens of the same ponyfish species, for the two species in which specimens of both sexes were examined. These observations raise the possibility that specific variations in the bacteriocupreins of P. leiognathi might be characteristic of the species, geographical source, or sex of the ponyfish host. Thus, the data indicate that the possibility of strain variation should be considered when other species are screened for bacteriocupreins.